Plasticity of the Central Nervous System Involving Peripheral Nerve Transfer - Jun Shen (Neural Plasticity)
Peripheral nerve injury can lead to partial or complete loss of limb function, and nerve transfer is an effective surgical salvage for patients with these injuries. The inability of deprived cortical regions representing damaged nerves to overcome corresponding maladaptive plasticity after the reinnervation of muscle fibers and sensory receptors is thought to be correlated with lasting and unfavorable functional recovery. However, the concept of central nervous system plasticity is rarely elucidated in classical textbooks involving peripheral nerve injury, let alone peripheral nerve transfer. This article is aimed at providing a comprehensive understanding of central nervous system plasticity involving peripheral nerve injury by reviewing studies mainly in human or nonhuman primate and by highlighting the functional and structural modifications in the central nervous system after peripheral nerve transfer. Hopefully, it will help surgeons perform successful nerve transfer under the guidance of modern concepts in neuroplasticity.